2017
DOI: 10.1039/c7fo00932a
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fucoidan of Acaudina molpadioides alters gut microbiota and mitigates intestinal mucosal injury induced by cyclophosphamide

Abstract: Cyclophosphamide (cy) is a widely used cancer drug. Many researchers have focused on the prevention and alleviation of its side effects, particularly damage to the intestinal mucosal barrier. In this study, we examined the effects of fucoidan, isolated from Acaudina molpadioides, on mice with intestinal mucosal damage induced by cyclophosphamide. Our results showed that fucoidan intervention could relieve injury such as decreasing inflammation and increasing the expression of tight junction proteins, and 50 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 38 publications
4
83
1
Order By: Relevance
“…Our ndings were consistent with the previous studies that mushroom polysaccharides shaped the overall structure of gut microbiota [8,31]. Similarly, CTX was reported to stimulate the proliferation of pathogens and reduction of friendly bacteria [32]. On the one hand, as the primary phyla of the gut microbiota, Bacteroidetes and Firmicutes can utilize carbohydrate active enzyme to break down carbohydrates but the degradation of polysaccharides mostly depends on Bacteroidetes [33].…”
Section: Effect Of Pog On the Intestinal Mucosal Barrier In Ctx-inducsupporting
confidence: 92%
See 1 more Smart Citation
“…Our ndings were consistent with the previous studies that mushroom polysaccharides shaped the overall structure of gut microbiota [8,31]. Similarly, CTX was reported to stimulate the proliferation of pathogens and reduction of friendly bacteria [32]. On the one hand, as the primary phyla of the gut microbiota, Bacteroidetes and Firmicutes can utilize carbohydrate active enzyme to break down carbohydrates but the degradation of polysaccharides mostly depends on Bacteroidetes [33].…”
Section: Effect Of Pog On the Intestinal Mucosal Barrier In Ctx-inducsupporting
confidence: 92%
“…The metabolites of gut microbiota, especially for SCFAs, had relevance for immunosuppression pathogenesis [32]. Acetic acid was the primary SCFAs and its physiological function could be exerted after being oxidized by intestinal tract [44,45].…”
Section: Effect Of Pog On the Intestinal Mucosal Barrier In Ctx-inducmentioning
confidence: 99%
“…Total RNA from intestinal samples was extracted as previously described [66]. The concentration of each extracted RNA sample was determined using a Nano Drop 2000 Spectrophotometer (Thermo, USA), and the integrity of the RNA was checked using denatured RNA electrophoresis.…”
Section: Real-time Qpcrmentioning
confidence: 99%
“…The epithelial leucocytes and goblet cells of the digestive tract contribute to barrier defence of intestine against invading pathogens (Birchenough, Johansson, Gustafsson, Bergstrom, & Hansson, ; Rauta, Nayak, & Das, ). Recent studies indicated that dietary fucoidan modulates the gut microbiota and has protective effects on intestinal mucosal barrier damage in mice (Shang et al, ; Shi et al, ). Similarly, several studies reported that supplementation of fucoidan improves gut health of pig by modulating gastrointestinal architecture, nutrition digestibility and intestinal microflora (Heim et al, ; Lynch, Sweeney, Callan, O'Sullivan, & O'Doherty, ; McDonnell, Figat, & O'Doherty, ; Walsh, Sweeney, O'Shea, Doyle, & O'Doherty, ).…”
Section: Introductionmentioning
confidence: 99%